Intimate Partner Violence and Barriers to Help-Seeking Among Black, Asian, Minority Ethnic and Immigrant Women: A Qualitative Metasynthesis of Global Research. (April 2023) - Hulley, Joanne; Bailey, Louis; Kirkman, Gill; Gibbs, Graham R.; Gomersall, Tim; Latif, Amrana; Jones, Adele
It is well known that victims of intimate partner violence experience numerous barriers to leaving abusive relationships. For ethnic minority and immigrant women these barriers are significantly exacerbated. This metasynthesis explored barriers to help-seeking as experienced by Black, Asian, minority ethnic and immigrant women with experience of intimate partner violence. A review of worldwide literature published in English in peer-reviewed journals on this topic from 2000 to July 2020 produced 2597 relevant articles. After removing duplicates and applying the exclusion criteria, a total of 47 articles were selected for inclusion in the review. The synthesis found that these women faced additional barriers as a result of institutional racism, immigration laws, culture and religion, and issues of cultural competence, and lack of diversity within frontline services. Such barriers, from a range of formal and informal resources, services and other mechanisms of support, served to exacerbate feelings of fear, threat, isolation and powerlessness. The barriers were also further weaponised by perpetrators in order to extend their reign of terror and control. As a result, women were caught in a double-bind – stay in an abusive relationship or face further threats and consequences if they attempted to leave. Whilst our search criteria focused on barriers to help-seeking, many of the papers included in our synthesis also explored facilitators to help-seeking, which are included in our findings and overwhelmingly relate to informal support from females.